Adenosine Metabolism in COPD: A Study on Adenosine Levels, 5′-Nucleotidase, Adenosine Deaminase and Its Isoenzymes Activity in Serum, Lymphocytes and Erythrocytes. (2nd November 2018) - Singh Patidar, Bhagwan; Meena, Anil; Kumar, Manoj; Menon, Balakrishnan; Rohil, Vishwajeet; Kumar Bansal, Surendra
Abstract: Adenosine is a signaling molecule which is produced in high concentrations during airway inflammation. Airway inflammation is a characteristic feature of COPD. Therefore, the current study was designed to evaluate the changes in adenosine metabolism in COPD and correlate these changes with severity of the disease. The study was conducted on 50 healthy controls (25 healthy non-smokers and 25 healthy smokers) and 46 COPD patients (21 moderate, 15 severe and 10 very severe). The patients were sub-divided into moderate, severe and very severe categories as per the GOLD spirometric classification. Blood was collected from each subject and serum, lymphocytes and erythrocytes were separated. The adenosine levels and activities of 5′-nucleotidase, adenosine deaminase and its isoenzymes were assessed in serum, lymphocytes and erythrocytes. The data were analyzed statistically. A p value < 0.05 was considered as significant. In healthy smokers and COPD patients the adenosine levels increased. In COPD patients 5′-nucleotidase activity increased significantly in serum, lymphocytes and erythrocytes. The activities of ADA and isoenzymes decreased significantly in serum of healthy smokers and COPD patients, in lymphocytes and erythrocytes of very severe COPD patients and of ADA and ADA2 in lymphocytes and erythrocytes of moderate and severe COPD patients. The FEV1 (% of predicted) showed a significant negative correlation with adenosine levels and 5′-nucleotidase activity in serum, lymphocytes and erythrocytes and significant positive correlation with ADA and isoenzymes activity in serum and lymphocytes of COPD patients. We conclude that the adenosine metabolism changes in COPD. The adenosine levels and 5′-nucleotidase activity increase, and ADA activity decreases with severity of the disease.